A COMPARATIVE STUDY OF ChatGPT AND GEMINI AS AI TOOLS FOR INSTAGRAM CONTENT IDEATION IN SMALL BUSINESS - Gilbert Soekwanto; Tuty Lindawati; Yuliasti Ika Handayani (Sahid University Jakarta, 2026)
Digital marketing through Instagram demands a high level of content consistency; however, this remains a major challenge for micro-enterprises due to limited resources. Generative Artificial Intelligence (AI) technologies, such as ChatGPT and Gemini, offer potential solutions to enhance efficiency, yet their specific effectiveness in addressing the needs of micro-businesses remains underexplored. This study aims to comparatively analyze the quality, relevance, and utility of content ideas generated by these two platforms based on the perceptions of micro-entrepreneurs. A qualitative descriptive approach was employed, with data collected through in-depth interviews and live experimental sessions involving nine micro-enterprise owners in Indonesia, selected via purposive sampling. The data were analyzed using thematic analysis supported by MAXQDA software to identify dominant preference patterns. The findings reveal that the majority of participants (7 out of 9) preferred ChatGPT, citing its strengths in producing a more natural tone of voice, effective role-playing capabilities, and detailed visual scripting. In contrast, Gemini demonstrated advantages in data validity, localization (i.e., understanding of local cultural context), and the systematic presentation of information in tabular formats. The study concludes that execution efficiency and ease of use are the primary determinants for micro-enterprise users. Accordingly, a hybrid strategy is recommended: utilizing Gemini for research and planning stages, and ChatGPT for creative content production.